Overview of public-private partnerships in the waste-to-energy incineration industry in China: Status, opportunities, and challenges. (November 2020) - Cui, Caiyun; Liu, Yong; Xia, Bo; Jiang, Xiaoyan; Skitmore, Martin
Abstract: To accommodate the rapidly increasing amount of municipal solid waste (MSW) sustainably and effectively, public-private partnership (PPP) waste-to-energy (WTE) incineration has achieved rapid growth in China. This study provides an insight into current practice and identifies key opportunities and major challenges in the further development of PPP implemented in China's WTE incineration industry. The results show that the public-private-partnership market is currently under a period of rapid expansion, with a large number of well-funded and highly professional public-private partnership suppliers emerging in recent decades, but at a level of market concentration that is significantly lower than in mature markets such as in the United States and Japan. Meanwhile, excellent market potential and preferential policies, as well as booming technological innovations, provide sufficient motivation for further development. However, the quality and quantity of municipal solid waste supplied, emerging public opposition, policy changes and the development dilemmas involved are major challenges to the sustainable and healthy development of the waste-to-energy incineration industry in China. These findings make strong contributions and have both theoretical and practical implications for researchers and practitioners, including policymakers and incineration professionals in the PPP WTE incineration industry. Highlights: An overview of public-private partnerships in China's waste-to-energy industry was conducted. The waste-to-energy incineration market is currently under a period of rapid expansion. The market, policies, and technological innovations motivate its further development. Waste supply, public opposition, policy changes and development dilemmas affect its current performance.